Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Paser - Harmayanto Harmayanto; Tegen Sayuk Rimboko; Chairun Nisa (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The purpose of this study is to determine the influence of leadership styles (X) consisting of directive leadership styles (X1), supportive leadership (X2), participative leadership (X3), and achievement-oriented leadership (X4) on employee performance (Y) at the Paser Regency Education and Culture Office. The results of multiple linear regression analysis obtained a regression equation, namely: Y = 2.048 + 0.583x1 + 0.294X2 + 0.361X3 + 0.045X4. The correlation coefficient (R) value of 0.755 means that the directive leadership style (X1), supportive leadership (X2), participative leadership (X3), achievement-oriented leadership (X4) shows a strong relationship with the Employee Performance variable (Y). The coefficient value (Adjusted R²) of 0.502 means that the variables of directive leadership style (X1), supportive leadership (X2), participative leadership (X3), achievement-oriented leadership (X4) contribute to employee performance (Y) at the Department of Education and Culture by 50.2%, while the remainder is contributed by other factors not studied by (100-50.2)% = 48.2%. The simultaneous results (F test) show that the F count value > F table (8.297 > 2.76) so it can be concluded that the variables of directive Leadership style (X1), Supportive Leadership (X2), Participative Leadership (X3), Achievement-oriented Leadership (X4) have an effect on Employee Performance (Y) at the Paser Regency Education and Culture Office. Furthermore, the results of the partial test (t test) show that the t count value of Variable (X) that has a significant effect is the directive Leadership style (X1) because t count > t table (3.756 > 2.05954). So that Directive Leadership (X1) has a dominant effect on Employee Performance (Y) at the Paser Regency Education and Culture Office.